TEACHER READINESS FOR INNOVATION IN EDUCATION: COMPONENTS, CHALLENGES, AND STRATEGIES FOR EFFECTIVE IMPLEMENTATION (ІННОВАЦІЙНІ ПРОЦЕСИ ОСВІТНЬОЇ СФЕРИ УКРАЇНИ ТА КРАЇН ЦЕНТРАЛЬНОЇ ЄВРОПИ: СТАН, ПРОБЛЕМИ І ПЕРСПЕКТИВИ, 2024)
.